IN ANCIENT TIMES, THE SYSTEM OF COMMUNICATION WITH THE PEOPLE WAS THE FIRST DEMOCRATIC ELEMENT - Dilmurod Mamatkulov (Western European Studies, 2025)
This article analyzes the communication system established among the peoples of ancient Turan and evaluates it as an early manifestation of democratic principles. The research draws on historical sources, archaeological findings, legendary narratives, and ancient written monuments to explore mechanisms that facilitated public address, the expression of popular opinion, and broad participation in decision-making processes. The study examines forms of socio-political dialogue—such as tribal assemblies, people's councils, and the council of elders—that functioned in ancient times, revealing their democratic foundations. Furthermore, the article investigates the historical roots and connections of these systems with contemporary civil society institutions. The traditions of dialogue within Turan's cultural heritage are interpreted as early forms of popular governance.
Keywords: Turan region; ancient communication system; public dialogue